Usefulness of Urinoculture to Patients With Dementia and Femoral Neck Fracture at Admission to Hospital: Preliminary Results. (March 2017) - Garcia-Nuño, Laura; Villamil, Carlos; González-Cuevas, Araceli; Martí, David; Capilla, Silvia; Vives, Maria José; Oncins, Xavier; Torner, Pere; Castellanos, Juan; Font-Vizcarra, Lluís
Introduction: While preoperative urinary tract infection (UTI) has the potential to cause bacteremia and postsurgical acute prosthetic joint infections (APJIs), the influence of asymptomatic bacteriuria (AB) in these infections remains unclear. So the majority of guidelines not recommend the treatment of AB prior to the surgery. However, as patients with dementia usually cannot explain the symptoms of dysuria, the differential diagnosis between AB and UTI may be very difficult in this group of patients. The principal aim of the study was to compare the rate of positive urine culture at admission in patients with femoral neck fracture with and without dementia and secondarily try to assess the connection of positive urinoculture and postoperative acute gram-negative PJI. Methods: All patients with a femoral neck fracture underwent a urine culture on hospital admission and were prospectively recorded. Variables such as sex, age, institutionalization, dementia and other comorbidities, PJI rate, and in-hospital death were collected. The results of cultures were retrospectively revised. Patients who received postoperative antibiotics or had been diagnosed with UTI during hospital stay were excluded. Statistical comparisons between patients with and without dementia were performed using SPSS software version 17. Results: A total of 148 patients were included (52 with dementia). The rate of positive urine culture was 32% (n = 16) in patients with dementia and 11.5% in patients without dementia ( P = .003). Of these 16 patients with dementia and positive urine culture, 2 (12.5%) developed an acute gram-negative PJI, whereas there were no cases in the group without dementia ( P = .011). Discussion: The only difference between UTI and AB is the expression of symptoms by the patient. However, as patients with dementia have difficulties to explain UTI symptoms, some UTI may be underdiagnosed. Conclusion: Patients with dementia have a statistically higher rate of presurgical positive urine culture compared with patients without dementia.